The Influence of a Scientific Approach to Improve Students’ Mathematical Understanding Ability - febrianti, ismaya; Erna Suwangsih; Puji Rahayu (Jurnal Pendidikan dan Kebudayaan Missio, 2025)
Mathematics is important to be taught to children, starting from elementary school to high school. Mathematics can help students to develop the ability to understand, reason, solve problems, communicate, and develop students' curiosity. Elementary school students need to have understanding skills, one of which is mathematical understanding. Currently, students' mathematical understanding skills are not optimal because students lack enthusiasm in learning, learning has not involved the role of students actively, and students feel that math is difficult. Based on this situation, there needs to be an alternative that can overcome students' difficulties in learning mathematics, namely by applying a scientific approach. This study aims to determine the effect and improvement of the application of the scientific approach to the mathematical understanding ability of the presentation and interpretation of data in class IV SDN 6 Nagrikaler. The samples used in this study were grade IV A and C students of SDN 6 Nagrikaler. The type of research in this study is Quasi Experiment with a non-equivalent control group design. This study resulted in an increase in the average experimental class better than the control class and the magnitude of the influence of the scientific approach on students' mathematical understanding ability of 41.1%. So it can be concluded that there is an increase and a good influence from the application of the scientific approach to students' mathematical understanding ability. Thus, the scientific approach can be used in grade IV learning, especially the presentation and interpretation of data.